2021
DOI: 10.1155/2021/8812542
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Artificial Intelligence (AI) in Education from 2010 to 2020

Abstract: This study provided a content analysis of studies aiming to disclose how artificial intelligence (AI) has been applied to the education sector and explore the potential research trends and challenges of AI in education. A total of 100 papers including 63 empirical papers (74 studies) and 37 analytic papers were selected from the education and educational research category of Social Sciences Citation Index database from 2010 to 2020. The content analysis showed that the research questions could be classified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 382 publications
(173 citation statements)
references
References 104 publications
0
73
0
8
Order By: Relevance
“…Artificial intelligence (AI) technology is applied to promote learning and teaching effectiveness (Lim, 2020). AI technology is being used to monitor teaching processes and to perform academic analysis and academic level diagnosis (Zhai et al, 2021). Thus, reconstructing an AI-assisted learning environment with interactive and smart learning has become a new task in education.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence (AI) technology is applied to promote learning and teaching effectiveness (Lim, 2020). AI technology is being used to monitor teaching processes and to perform academic analysis and academic level diagnosis (Zhai et al, 2021). Thus, reconstructing an AI-assisted learning environment with interactive and smart learning has become a new task in education.…”
Section: Introductionmentioning
confidence: 99%
“…In a review about the AI in education, Zhai et al (2021) identified that the ethics of AI are relevant in education. However, our participants' concerns focused more on social skills and related ethical concerns and not so much on practical solutions.…”
Section: Discussionmentioning
confidence: 99%
“…The use of AI technologies to enhance students' learning experiences has gained increasing popularity, especially in the last decade (Chassignol et al, 2018;Aslan et al, 2019;Jia et al, 2020;Baker, 2021;Zhai et al, 2021;Zhang and Aslan, 2021). Intelligent gamebased learning systems (Lester et al, 2013;Richey et al, 2021) present significant benefits for practicing math concepts in smart spaces (Pires et al, 2019;Sun et al, 2021), specifically for early childhood education (Skene et al, 2022).…”
Section: Related Workmentioning
confidence: 99%
“…Investigating Artificial Intelligence (AI) systems that can help children in their learning process has been a challenging yet exciting area of research (Chassignol et al, 2018;Zhai et al, 2021). Utilizing Natural Language Processing (NLP) for building educational games and applications has gained popularity in the past decade (Lende and Raghuwanshi, 2016;Cahill et al, 2020).…”
Section: Introductionmentioning
confidence: 99%